Ascending from the valley: Can state-of-the-art photorealism avoid the uncanny? - Mc Donnell, Rachel (My University, 2021)
Advancements in real-time rendering technology have continued to develop rapidly over the course of the last decade. Consequently, human likenesses have been represented virtually with increasingly impressive detail. There is evidence that this increased resemblance to real humans has an observable and wide-ranging set of effects on human perception, cognition and action in situations that in volve digital characters. Studies that seek to advance the science of synthetic animated people have consistently aimed to measure and quantify changes in perceived emotional content mediated through artificial human likenesses
PUBLISHED
Keywords: real-time rendering technology; digital characters; virtual humans; Network reliability; Embedded systems; Robotics; Redundancy